ASHRAE design guide for tall, supertall, and megatall building systems - Simmonds, Peter, 1954- (ASHRAE, 2020)
"The ASHRAE Design Guide for Tall, Supertall, and Megatall Building Systems, second edition, is concerned with HVAC, design, maintenance, and other factors for buildings 330 feet (100 m) or higher. The guide details the problems and possible solutions for tall, supertall, and megatall buildings"--